Children’s literature as coupling point between global sustainability concerns and children’s local agency - Marie Kolmos; Anna Karlskov Skyggebjerg; Anne Maj Nielsen (Nordisk Barnehageforskning)
This article is about how educators’ dialogical–creative presentation of children’s picture books has the potential to make global sustainability concerns accessible to young children. Thematization around climate change and the biodiversity crisis are global phenomena that are difficult to translate to the local settings where children spend part of their lives. This article argues that various dialogical and creative reading activities based on relevant children’s literature may serve as gateways to developing young children’s agency and understanding related to some of the sustainability concerns that they may have to address when they grow up. This article’s analysis is based on two literature courses at a Danish early childhood education and care centre, where educators invited children to creatively explore literary narratives in various ways, through visits to the surrounding area and the creative processing of the stories’ message. The analyses show how children’s potential agency is developed through a dialectical process of becoming based on a sociocultural and phenomenological understanding of artefacts, mediating means and place as an event.